Comparative study on effects of injection mode on combustion and emission characteristics of a combined injection n-butanol/gasoline SI engine with hydrogen direct injection. (15th December 2020) - Shang, Zhen; Yu, Xiumin; Ren, Lei; Wei, Guowu; Li, Guanting; Li, Decheng; Li, Yinan
Abstract: In this paper, on the basis of combined injection technique, three injection modes with five n-butanol/gasoline volume ratios ( ν N ) were put forward, aiming to compare and evaluate the relationship between the injection mode and the combustion and emission characteristics of an n-butanol/gasoline SI engine equipped with an extra hydrogen direct injection system. The results indicated that under low load condition, compared with NGP (n-butanol/gasoline port injection) mode, the NGPD (n-butanol/gasoline combined injection) mode and NGPH (n-butanol/gasoline with hydrogen combined injection) mode can both improve the combustion performance. The peak cylinder pressure of NGPD and NGPH mode was 5.58% and 11.63% higher than that of NGP mode on average, respectively. Furthermore, the combined injection modes concentrated the process of heat release, shortened the combustion duration, increased the power performance and improved the combustion stability at all ν N . As for emissions, the NGPD and NGPH combined modes significantly decreased the HC and CO emissions, but increased the NOX emissions. Among all the test conditions, the NGPH mode with 25% ν N obtained the best combustion quality. Additionally, the effect rules of ν N on combustion and emission characteristics under NGP mode were found to be consistent with those under NGPD and NGPH combined modes. Highlights: An n-butanol/gasoline SI engine with hydrogen direct injection is proposed. The low load performance versus n-butanol ratio under 3 injection modes are compared. The change of combustion parameters with n-butanol ratio is consistent under 3 modes. Combined injection and hydrogen can make up for the innate issues of n-butanol.